Sprejeti med prijatelji, zavrnjeni v družbi - istospolna partnerstva v Sloveniji - Švab, Alenka (Družboslovne razprave, 2005)
The article deals with the analysis of everyday life of gays and lesbians in Slovenia with the attempt to answer the question whether we can speak of transformation of intimacy and pure relationship among gays and lesbians. The analysis is done on the basis of data from the first sociological research on everyday life of gays and lesbians in Slovenia, carried out with the combination of quantitative and qualitative methodology (survey and focus groups). The main idea of the article is that in some characteristics (e.g. egalitarian division of labour, reflexive relationship, constant work on relationship etc.) same-sex relationships are similar to "pure relationships", however gay and lesbian relationships are importantly defined by the heteronormative framework of the broader society in which they live. According to authorćs opinion we cannot speak of transformation of intimacy going on in the same way for heterosexuals and homosexuals. The author claims that there is a specific situation (at least in Slovenia). On the one hand, there is a high level of homophobia and violence against gays and lesbians in public space, on the other hand, homosexuality is being privatised and closed up in private space of friends, intimate partners, and to some extent family members, who accept homosexual orientation of their children more and more positively.
Keywords: spolna identiteta; homoseksualnost; homosexuality; homoseksualci; družbeno vedenje; social psychology; socialna psihologija; družbebna izključenost; Slovenia; Slovenija